2021
DOI: 10.18502/ijph.v50i5.6103
|View full text |Cite
|
Sign up to set email alerts
|

Basic Criteria, Models, and Indicators of Intersectoral Collaboration in Health Promotion: A Scoping Review

Abstract: Background: In this study, the basic criteria, models, and indicators of intersectoral collaboration in health promotion were investigated to facilitate the implementation of collaboration. Methods: This scoping review was conducted using datasets of Embase, Web of Science, Scopus, and PubMed, and search engines of Google, Google Scholar, and ProQuest. Results: 52 studies were included, and 32 codes in Micro, Meso, and Macro level, were obtained. Micro-level criteria had the highest frequency. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(46 reference statements)
0
4
0
1
Order By: Relevance
“…Some authors have provided general models for ISC. One of these models is the Bergen Model of Collaborative Functioning (BMCF), which was developed to produce synergy from collaborative health promotion ( 20 , 73 75 ). Diagnosis of Sustainable Collaboration (DISC) is another model that is used for health promotion ( 76 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have provided general models for ISC. One of these models is the Bergen Model of Collaborative Functioning (BMCF), which was developed to produce synergy from collaborative health promotion ( 20 , 73 75 ). Diagnosis of Sustainable Collaboration (DISC) is another model that is used for health promotion ( 76 ).…”
Section: Resultsmentioning
confidence: 99%
“…A review of the international literature carried out in 2018 by Corbin (25) responded to the objective of identifying alliance processes on health promotion, finding 26 studies carried out between 2007 and 2015, a period of 8 years, mostly from the United States, and none on LAC. Another similar review about health promotion was developed by Reza (26) in 2021 to map the existing literature between 2001 and 2015 about intersectorality and the HIAP approach and finding 52 articles in the review according to the established inclusion criteria; most studies come from the United States, again, and to a smaller extent, from Germany, Canada, and Australia. Among the LAC countries, only Brazil is found, with only one study.…”
Section: Discussionmentioning
confidence: 99%
“…According to [3][36], collaboration comes from many levels: • Coexistence: IS don't know each other • Networking: each IS is aware of the existence of other spaces • Cooperation: each one has identified common interests and occasionally carries out operations together • Partnership: they occasionally carry out projects together in sharing roles, skills and risks to achieve a common goal and communicating regularly • Coordination: IS have similar operations and strategies [49][36] The first level is important. Indeed, it's necessary that the IS is extremely well defined [11] and knows its individual characteristics (innovation process, strategic intent, organization…) [1] before joining a network [50].…”
Section: B) Levels and Governance Of Collaborationmentioning
confidence: 99%
“…c) Performance Indicators Through our study, a literature review examining model, criteria and indicators of collaboration was identified [49]. After the analysis of the different existing network representations show in [49], we could see that the temporal and dynamic dimension of the network is rarely taken into account in these representations [28]. It will be necessary to include them for monitoring and evaluation.…”
Section: B) Levels and Governance Of Collaborationmentioning
confidence: 99%